Respuesta :
Answer:
[tex]\frac{2\sqrt{2}}{\sqrt{3}-\sqrt{2}}=2\sqrt{6}+4[/tex]
Step-by-step explanation:
We have the expression:
[tex]\frac{2\sqrt{2}}{\sqrt{3}-\sqrt{2}}[/tex]
To simplify the expression multiply by the conjugate of the denominator.
The denominator is
[tex]\sqrt{3}-\sqrt{2}[/tex]
Then its conjugate is:
[tex]\sqrt{3}+\sqrt{2}[/tex]
Then:
[tex]\frac{2\sqrt{2}}{\sqrt{3}-\sqrt{2}}*\frac{\sqrt{3}+\sqrt{2}}{\sqrt{3}+\sqrt{2}}\\\\=\frac{2\sqrt{2}\sqrt{3}+2\sqrt{2}\sqrt{2}}{(\sqrt{3})^2-(\sqrt{2})^2}\\\\\frac{2\sqrt{6}+4}{3-2}}\\\\= \frac{2\sqrt{6}+4}{1}}=2\sqrt{6}+4[/tex]
Answer:
[tex]4+2\sqrt{6}[/tex]
Step-by-step explanation:
Given expression is [tex]\frac{2\sqrt{2}}{\sqrt{3}-\sqrt{2}}[/tex].
Now we need to simplify this. So multiply and divide by conjugate of denominator.
[tex]\frac{2\sqrt{2}}{\sqrt{3}-\sqrt{2}}[/tex]
[tex]=\frac{2\sqrt{2}}{\left(\sqrt{3}-\sqrt{2}\right)}[/tex]
[tex]=\frac{2\sqrt{2}}{\left(\sqrt{3}-\sqrt{2}\right)}\cdot\frac{\left(\sqrt{3}+\sqrt{2}\right)}{\left(\sqrt{3}+\sqrt{2}\right)}[/tex]
[tex]=\frac{2\sqrt{6}+2\sqrt{4}}{\left(\sqrt{3}\right)^2-\left(\sqrt{2}\right)^2}[/tex]
[tex]=\frac{2\sqrt{6}+2\cdot2}{3-2}[/tex]
[tex]=\frac{2\sqrt{6}+4}{1}[/tex]
[tex]=2\sqrt{6}+4[/tex]
[tex]=4+2\sqrt{6}[/tex]
Hence final answer is [tex]4+2\sqrt{6}[/tex].